2023
DOI: 10.1007/s40618-023-02123-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype relationship and comparison between eastern and western patients with osteogenesis imperfecta

Abstract: Purpose To evaluate the genotypic and phenotypic relationship in a large cohort of OI patients and to compare the differences between eastern and western OI cohorts. Methods A total of 671 OI patients were included. Pathogenic mutations were identified, phenotypic information was collected, and relationships between genotypes and phenotypes were analyzed. Literature about western OI cohorts was searched, and differences were compared between eastern and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…As shown in previous studies, OI patients with biallelic variants often had severe phenotypes ( 4 ). OI type VII is an autosomal recessive form of OI caused by CRTAP mutations, which can lead to loss of the prolyl-3-hydroxylase complex and disturb the architecture of the type I collagen structure ( 6 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As shown in previous studies, OI patients with biallelic variants often had severe phenotypes ( 4 ). OI type VII is an autosomal recessive form of OI caused by CRTAP mutations, which can lead to loss of the prolyl-3-hydroxylase complex and disturb the architecture of the type I collagen structure ( 6 ).…”
Section: Discussionsupporting
confidence: 70%
“…Mutations in COL1A1 or COL1A2 lead to autosomal dominant OI through inducing quantitative deficiencies or structural defects of type I collagen ( 3 ). The remaining OI cases are caused by mutations in a variety of other genes, and patients with the recessive form of OI usually show more severe phenotypes, including more fractures, more severe skeletal deformities, shorter stature, and poorer mobility ( 4 ).…”
mentioning
confidence: 99%
“…The COL1A1 and COL1A2 mutations were among the most commonly reported. Other findings included the correlation between genotype and phenotype, depending on the mutation and the protein modification caused [47]. A group of investigators from Estonia, Vietnam, and Ukraine showed that 82 (56.16%) patients of all the 146 examined cases revealed pathogenic de novo variants.…”
Section: Discussionmentioning
confidence: 99%